Clinical value of different QRS-T angle expressions - Hnatkova, Katerina; Seegers, Joachim; Barthel, Petra; Novotny, Tomas; Smetana, Peter; Zabel, Markus; Schmidt, Georg; Malik, Marek (Europace, 2018)
AIMS: Increased spatial angle between QRS complex and T wave loop orientations has repeatedly been shown to predict cardiac risk. However, there is no consensus on the methods for the calculation of the angle. This study compared the reproducibility and predictive power of three most common ways of QRS-T angle assessment. METHODS AND RESULTS: Electrocardiograms of 352 healthy subjects, 941 survivors of acute myocardial infarction (MI), and 605 patients recorded prior to the implantation of automatic defibrillator [implantable cardioverter defibrillator (ICD)] were used to obtain QRS-T angle measurements by the maximum R to T (MRT), area R to T (ART), and total cosine R to T (TCRT) methods. The results were compared in terms of physiologic reproducibility and power to predict mortality in the cardiac patients during 5-year follow-up. Maximum R to T results were significantly less reproducible compared to the other two methods. Among both survivors of acute MI and ICD recipients, TCRT method was statistically significantly more powerful in predicting mortality during follow-up. Among the acute MI survivors, increased spatial QRS-T angle (TCRT assessment) was particularly powerful in predicting sudden cardiac death with the area under the receiver operator characteristic of 78% (90% confidence interval 63-90%). Among the ICD recipients, TCRT also predicted mortality significantly among patients with prolonged QRS complex duration when the spatial orientation of the QRS complex is poorly defined. CONCLUSION: The TCRT method for the assessment of spatial QRS-T angle appears to offer important advantages in comparison to other methods of measurement. This approach should be included in future clinical studies of the QRS-T angle. The TCRT method might also be a reasonable candidate for the standardization of the QRS-T angle assessment.
Keywords: dospělí; náhlá srdeční smrt; hodnocení rizik; Female; Adult; ženské pohlaví; elektrická defibrilace; mladý dospělý; Action Potentials; Death, Sudden, Cardiac; Predictive Value of Tests; Reproducibility of Results; prediktivní hodnota testů; lidé; Electric Countershock; studie případů a kontrol; Risk Assessment; Arrhythmias, Cardiac; Electrocardiography; elektrokardiografie; prognóza; srdeční frekvence; Middle Aged; Risk Factors; reprodukovatelnost výsledků; Male; Case-Control Studies; Aged; Young Adult; rizikové faktory; Myocardial Infarction; Prognosis; Defibrillators, Implantable; lidé středního věku; akční potenciály; senioři; mužské pohlaví; defibrilátory implantabilní; Heart Rate; srdeční arytmie; infarkt myokardu; Humans